TRAINING SOSIAL BERBASIS TEKNOLOGI DALAM KASUS BULLYING - Ni Gusti Made Rai; Ni Wayan Suarmini (JURNAL SOSIAL HUMANIORA (JSH), 2016)
This paper describe the bullying phenomenona and its alternative efforts to prevent it. Bullying is a form of negative behavior which is done subconsciously and repeatedly to his/her victim physically or non-physically. Weary and uncomfortable victims’ feelings elevate the domination and superiority of the bully. By an ecology approach, which involving microsystem, ecosystem. and microsystem, it is expected to recognize a prevention action which is more effective and comprehensive. Also, it needs a wider involvement and a thorough control from the community. The training that’s based on technology social is expected to be able to bridge the gap from the challenge given. Technology was not only viewed as a source of the problems, but can beused as a benefitted platform to develop and groom more pro-social behavior.